2020
DOI: 10.21037/tcr-20-1038
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prognostic value of intratumoral and peritumoral lymphangiogenesis in colorectal cancer

Abstract: Background: Colorectal cancer (CRC) with lymphatic invasion is one of the critical prognostic factors in lymph node metastasis. Lymphangiogenesis has a significant effect on lymphatic metastasis and tumor progression. However, the significance of intratumoral and peritumoral lymphangiogenesis has been controversial in CRC. The aim of this study is to investigate the different role of introtumoral and peritumoral lymphangiogenesis in CRC progression and prognosis.Methods: Lymphangiogenesis of 120 CRC specimens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Our studies describe a previously unknown pro-lymphangiogenic action of platinum chemotherapeutics. In vivo , we selected a dose of carboplatin that would not affect tumor growth and thus reduce confounding effects of tumor size and toxicity with lymphangiogenesis, as tumor size is correlated with changes to tumor stroma including lymphatics ( 46 , 47 ). In our pre-treatment animal models, we found that this led to enhanced metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies describe a previously unknown pro-lymphangiogenic action of platinum chemotherapeutics. In vivo , we selected a dose of carboplatin that would not affect tumor growth and thus reduce confounding effects of tumor size and toxicity with lymphangiogenesis, as tumor size is correlated with changes to tumor stroma including lymphatics ( 46 , 47 ). In our pre-treatment animal models, we found that this led to enhanced metastasis.…”
Section: Discussionmentioning
confidence: 99%